Astragalus Granule Prevents Ca2+ Current Remodeling in Heart Failure by the Downregulation of CaMKII. (10th August 2017) - Li, Sinai; Nong, Yibing; Gao, Qun; Liu, Jing; Li, Yan; Cui, Xiaoyun; Wan, Jie; Lu, Jinjin; Sun, Mingjie; Wu, Qian; Shi, Xiaolu; Cui, Haifeng; et al.
Abstract : Background . Astragalus was broadly used for treating heart failure (HF) and arrhythmias in East Asia for thousands of years. Astragalus granule (AG), extracted from Astragalus, shows beneficial effect on the treatment of HF in clinical research. We hypothesized that administration of AG prevents the remodeling of L-type Ca 2+ current (I C a - L ) in HF mice by the downregulation of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII). Methods . HF mice were induced by thoracic aortic constriction (TAC). After 4 weeks of AG treatment, cardiac function and QT interval were evaluated. Single cardiac ventricular myocyte was then isolated and whole-cell patch clamp was used to record action potential (AP) and I C a - L . The expressions of L-type calcium channel alpha 1C subunit (Cav1.2), CaMKII, and phosphorylated protein kinase A (p-PKA) were examined by western blot. Results . The failing heart manifested distinct electrical remodeling including prolonged repolarization time and altered I C a - L kinetics. AG treatment attenuated this electrical remodeling, supported by AG-related shortened repolarization time, decreased peak I C a - L, accelerated I C a - L inactivation, and positive frequency-dependent I C a - L facilitation. In addition, AG treatment suppressed the overexpression of CaMKII, but not p-PKA, in the failing heart. Conclusion . AG treatment protected the failing heart against electrical remodeling and I C a - L remodeling by downregulating CaMKII.